Malaysia : Technical Assistance Report-Government Finance Statistics Mission and Preceding Remote Support. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2019)
This technical assistance report on Malaysia explains the effort by the mission to support the Malaysian authorities in improving Government Finance Statistics (GFS) decision making. The mission achieved significant progress with respect to the development of a budgetary central GFS compilation system based on primary accrual accounting data. The mission, together with the authorities, successfully developed a compilation sheet to facilitate the largely automated compilation of a comprehensive set of GFS tables from the system. With respect to flows reported in the income statement, the analysis suggests that it is essential to build the survey around the balancing items (net) operative income and (net) comprehensive income. The analysis of the corporate balance sheets suggests that most accounting terms used by the public corporations can be grouped sensibly and linked to GFS classifications. With respect to the extrabudgetary units of central government, the mission proposed minor refinements of the survey and prepared preliminary GFS data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet